Genetic Redundancy in Rye Shows in a Variety of Ways - Alexander V. Vershinin; Evgeny A. Elisafenko; Elena V. Evtushenko (Plants, 2023)
Fifty years ago Susumu Ohno formulated the famous C-value paradox, which states that there is no correlation between the physical sizes of the genome, i.e., the amount of DNA, and the complexity of the organism, and highlighted the problem of genome redundancy. DNA that does not have a positive effect on the fitness of organisms has been characterized as “junk or selfish DNA”. The controversial concept of junk DNA remains viable. Rye is a convenient subject for yet another test of the correctness and scientific significance of this concept. The genome of cultivated rye, Secale cereale L., is considered one of the largest among species of the tribe Triticeae and thus it tops the average angiosperm genome and the genomes of its closest evolutionary neighbors, such as species of barley, Hordeum (by approximately 30–35%), and diploid wheat species, Triticum (approximately 25%). The review provides an analysis of the structural organization of various regions of rye chromosomes with a description of the molecular mechanisms contributing to their size increase during evolution and the classes of DNA sequences involved in these processes. The history of the development of the concept of eukaryotic genome redundancy is traced and the current state of this problem is discussed.